BASIC THEORY AND METHODOLOGY OF SOIL GEOPHYSICS: THE FIRST RESULTS OF APPLICATION - Menshov, O.; Sukhorada, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The magnetometric part of the geophysics of the pedosphere is the most developed one in its theoretical and practical aspects. We talk about three main problems facing pedomagnetology and humanity. This is an increase in the resource base, environment monitoring, and deep soil study, especially land degradation and productivity. The soil is a direct reflection of the processes occurring at the contact of the lithosphere and the atmosphere. There are two types of soils. The soils with residual magnetism have the magnetic properties related to their lithogenic base and processes of weathering. Much more investigated are the soils with the pedogenic magnetic signal origin. The iron oxides, hydroxides, and sometimes iron sulphides play the leading role in their magnetic behavior. The magnetic model of the soil horizons can significantly change under the anthropogenic and technogenic impact. Magnetic contrasts are associated with emission of vehicle, industrial enterprises, and power plants. Relief formation forces the slope erosion. These processes of change are related to the differentiation between soil horizons and soil magnetic properties. There are cases when magnetic minerals of sedimentary origin are formed above hydrocarbon deposits under the influence of fluid migration, which change the magnetic properties of the soil. The practical cases are considered in the examples.
Keywords: soil; environmental magnetism; theory and methodology; magnetic susceptibility